A new tool to assess amnestic mild cognitive impairment in Turkish older adults: virtual supermarket (VSM). Issue 5 (2nd September 2020) - Eraslan Boz, Hatice; Limoncu, Hatice; Zygouris, Stelios; Tsolaki, Magda; Giakoumis, Dimitrios; Votis, Konstantinos; Tzovaras, Dimitrios; Öztürk, Vesile; Yener, Görsev G.
ABSTRACT: The purpose of this study was to investigate cognitive functioning by administering the Virtual Supermarket (VSM) test in patients with amnestic mild cognitive impairment (aMCI, N = 37) and age and education-matched healthy controls (HCs, N = 52). An extensive neuropsychological test battery and the VSM were administered to all participants. The aMCI group exhibited lower performance and required more time to complete the VSM compared to HCs. Also, aMCI-Multiple Domain (aMCI-MD) patients performed worse in the "Correct Types", "Correct Quantities", "Bought Unlisted", "Correct Money" variables compared to HCs. Moreover, aMCI-SD patients displayed lower performance in "Bought Unlisted" and "Correct Money" variables compared to HCs. The VSM variables correlated with established neuropsychological test scores. The VSM test was found to discriminate between aMCI and HCs with a correct classification rate (CCR) of 81%. This is a preliminary study showing that the VSM is a valid, brief and user-friendly test. .